Romanians church of Transylvania during the period 1700-1764 (Confluenţe Bibliologice, 2025)
The author tackles the subject of Romanians from Transylvania who withstood several persecutions and unjustness thanks to two supports: moral ﬁrst, the second national consciousness. The practice of long Orthodox religion which around oppressed people gathered with great faith, in which the priests knew to conserve good religious rules and traditions but also to convey the hope of some happier days, constituted an important support. Another factor represents the national language and consciousness. The fact that they are not alone and their brothers from the two Romanian countries are beside them, constituting a nation, believe that has contributed to survive in unfavorable conditions. The topic is reﬂected in the chapters: Union with the Roman Catholic Church; the work of bishops Ion Micu (Klein), Inochentie Petru Paul Aron ; Metropolitan Serbian domination over Romanian Church of believers in Transylvania, the participation of the Romanian faithful at the seven years ‘ war with Prussia along with Austria; schools from Blaj; tearing down monasteries in Transylvania (Făgăraş District).
Keywords: religious education; architectural landmarks of Romania; Romanian Orthodox Church